System Design for Solid Waste Reuse: Fostering Sustainable Urbanism through the ReUseLink system - Kedar, Ori; Persov, Elad (European Journal of Sustainable Development, 2024)
This paper identifies three levels at which urban solid waste is generated: individual disposal of old objects, home renovations, and urban renewal projects. The increasing solid waste stream contributes to landfill use in rural and metropolitan areas, diminishing their ability to provide crucial ecosystem services to the city. To address this issue, qualitative research was conducted using project-based and design-thinking research and development methods. The paper presents solid waste generation and treatment research and develops a systemic behavioral, logistic, and digital solution. An online system connects municipal authorities, residents, and those interested in reuse, managing waste-producing processes, identifying the point of waste generation, and enabling logistical solutions for reuse. Emphasizing time management and object mapping, the system operates under the circular economy concept, generating financial and environmental profit. Furthermore, the system integrates waste management into the planning stages of renovation or renewal projects, allowing for proactive waste management considerations. Keywords: Sustainable system design, Sustainable Development, Twin Transition, New Urban Agenda